2019
DOI: 10.1021/acsearthspacechem.9b00070
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Origins of Thiols in Deep Strata Crude Oils, Tarim Basin, China

Abstract: Thiols (or mercaptans) in crude oils have been considered to be associated with thermochemical sulfate reduction (TSR). However, the molecular composition and the formation mechanism of thiols in crude oils are not clear. This study provides the molecular composition of thiols in several deep strata condensate oils (condensates) from the Tarim Basin. Selective Michael addition products of thiols were characterized using Fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) and comprehensive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Thiols in crude oil are thought to form when TSR-generated H 2 S reacts with petroleum hydrocarbons. High concentration of H 2 S in the associated natural gas created the necessary conditions for thiol formation. , More importantly, once again, the local burial and thermal history created appropriate conditions for the preservation of these thermally labile thiols. In other words, TSR alteration gradually ceased because of the uplift and cooling of the formation after the Early Cretaceous.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Thiols in crude oil are thought to form when TSR-generated H 2 S reacts with petroleum hydrocarbons. High concentration of H 2 S in the associated natural gas created the necessary conditions for thiol formation. , More importantly, once again, the local burial and thermal history created appropriate conditions for the preservation of these thermally labile thiols. In other words, TSR alteration gradually ceased because of the uplift and cooling of the formation after the Early Cretaceous.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The column was eluted with 6 mL n -hexane/DCM (2/1, v / v ), 12 mL of n -hexane/DCM (1/2, v / v ), and 6 mL of DCM in sequence to yield eluting solvents sequentially to yield the initial fraction, middle fraction, and final fraction. The previous results indicated that all thiol derivatives generated in the reaction were enriched in the middle fraction. , Hereinafter, the thiol derivatization products, by default, refer to the corresponding enriched fractions (middle fraction), which were characterized using FT-ICR MS.…”
Section: Samples and Methodsmentioning
confidence: 99%
“…Similar to thiadiamondoids, diamondoidthiols have also been found to be orders of magnitude more abundant in TSR-altered oils than in unaltered oils. These compounds have a distribution similar to that of their thiadiamondoid analogs. , Zhu et al investigated the molecular composition of thiols in several deep strata condensate oils from the Tarim Basin that suffered severe TSR alteration. It was determined that the carbon number and DBE ranges of the thiols are between 4–20 and 0–10, respectively.…”
Section: Composition Of Sulfur Compounds In Petroleummentioning
confidence: 99%
“…(a) Proposed formation pathways for low-molecular-weight thiols with carbon numbers ≤ 3; (b) proposed formation mechanism for thiols with carbon numbers > 3 and diamondoidthiols. Reprinted with permission from ref . Copyright 2019 American Chemical Society.…”
Section: Composition Of Sulfur Compounds In Petroleummentioning
confidence: 99%